Health and Distributional Impacts of a Tax on Sugar-Sweetened Beverages in Kazakhstan - Fuchs, Alan (World Bank, Washington, DC, 2020)
The promotion of healthy diets is at the center of many strategies to prevent and control noncommunicable diseases (NCDs) worldwide. Sugar-sweetened beverages (SSB) are the target of many of these strategies given their contribution to obesity and related diseases. In addition to detrimental health effects, overconsumption of SSBs can result in economic costs derived from health care expenditures, forgone productivity, permanent disability, and premature death. The World Health Organization (WHO 2017a) has concluded that one of the most effective tools for reducing obesity rates and other related NCDs is the implementation of taxes to increase the prices of SSBs by at least 20 percent. Epidemiological models indicate that taxing SSBs by sugar content could result in a 200 million-pound (90.7 million kilogram) weight reduction worldwide (Grummon, et al. 2019). This report represents the first adaptation of the extended cost-benefit analysis methodology to examine taxes on SSBs. The main outcome of interest is the net effect of the taxes on household income via three channels: (1) larger amount of household budget expenditure on SSBs, (2) savings in out-of-pocket (OOP) spending on health care because of lower disease incidence associated with reduced SSB consumption, and (3) higher labor income resulting from an increase in life-expectancy. The model uses the simplified assumption that a reduction in the consumption of SSBs has an immediate effect on health and so on employment-related income.